Pengaruh Penggunaan Internet Dalam Belajar, Minat Membaca Dan Manajemen Waktu Terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS SMA Negeri 1 Lubuk Basung - Reni Julita; Marwan Marwan (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the use of the internet in learning, reading interest and time management on economic learning outcomes of students of class X IPS SMA Negeri 1 Lubuk Basung both silmutanously and partially. This type of research uses causal associative with a quantitative approach. The research sample consisted of 62 students, the research sample was taken using probability random sampling technique using Slovin formula. Based on the results of the study it can be concluded that the use of the internet in learning, reading interest and time management simultaneously has a positive and significant effect on the economic learning outcomes of students of class X IPS of SMA Negeri 1 Lubuk Basung as evidenced by a significance value of 0,000 < 0.05 and a coefficient of determination of 0.389 or 38 9% ,. In the t test the use of the internet in learning partially has a positive and significant effect on economic learning outcomes of students of class X IPS SMA Negeri 1 Lubuk Basung as evidenced by the significance value of 0.043 < 0.05, and the interest in reading partially has a positive and significant effect on student economic learning outcomes IPS class X of SMA Negeri 1 Lubuk Basung is proven with a significance value of 0.008 < 0.05, while time management partially has a positive and not significant effect on economic learning outcomes of students of class X IPS SMA Negeri 1 Lubuk Basung as evidenced by the significance value of 0.127> 0.05. Keyword: internet usage, interest in reading, time management, economic learning outcomes